Chiral liquid crystal superstructure for luminous object charge regulation and control and preparation method and application of chiral liquid crystal superstructure
By controlling the charge type and charge density of non-chiral luminescent objects, the problem of the lack of left-handed CPL in chiral liquid crystal superstructures was solved, enabling the same superstructure to generate left-handed and right-handed CPLs on the front and back sides respectively, which can be applied to advanced anti-counterfeiting labels.
Patent Information
- Application Number
- CN202511672342.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-03-17
AI Technical Summary
Existing chiral liquid crystal superstructures can only achieve right-handed CPL, lacking left-handed CPL characteristics, which limits their application in the field of circularly polarized light emission.
By controlling the surface charge type and charge density of non-chiral light-emitting objects, the self-assembly dynamics of chiral CNC liquid crystals are controlled, and liquid crystal superstructures capable of generating left-handed and right-handed CPLs on the front and back sides of the same superstructure are prepared.
The circularly polarized luminescence properties of chiral liquid crystal superstructures were controlled, breaking through the traditional single rotation limitation, and an environmentally friendly advanced anti-counterfeiting label was prepared.
Smart Images

Figure CN121673652A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of circularly polarized luminescent materials technology, specifically to a chiral liquid crystal superstructure with luminescent guest charge control, its preparation method, and its application. Background Technology
[0002] Circularly polarized emission (CPL), as an important chiral optical property of chiral luminescent systems, can quantitatively characterize the difference in emission intensity between left-handed (L-) and right-handed (R-) circularly polarized light. Based on this property, CPL materials have potential applications in three-dimensional displays, circularly polarized light-emitting diodes (LEDs), polarization-based information encryption, asymmetric synthesis, and biomedicine, attracting widespread attention.
[0003] Currently, there are two main strategies for constructing CPL materials: one is to synthesize intrinsic chiral nanomaterials; the other is to introduce luminescent guests into chiral templates for ordered assembly, such as helical polymers, chiral metal-organic frameworks (MOFs), and cholesteric liquid crystals. Compared to intrinsic chiral nanomaterials, introducing luminescent guests into chiral templates, especially cholesteric liquid crystal templates, can significantly amplify the CPL signal, achieving a value greater than 10. -1 The luminescence asymmetry factor (g) lum ).
[0004] Among various cholesteric liquid crystal templates, cellulose nanocrystals (CNCs) have attracted much attention due to their abundant sources, high sustainability, biodegradability, and low cost. CNCs can be acid-hydrolyzed to obtain stable colloidal dispersions with negatively charged surfaces. The electrostatic repulsion and entropy effect of the system work together to spontaneously form left-chiral cholesteric liquid crystal structures. However, due to their singular chirality limitation, the prepared chiral liquid crystal superstructures can only achieve right-handed CPL; the lack of left-handed CPL characteristics restricts the application of chiral liquid crystal superstructures in the field of circularly polarized luminescence. Summary of the Invention
[0005] This application provides a chiral liquid crystal superstructure with luminescent guest charge control, its preparation method, and its application. By controlling the surface charge type and charge density of the non-chiral luminescent guest, the self-assembly dynamics of the chiral CNC liquid crystal are controlled, thereby achieving the control of the final chiral superstructure and its circularly polarized luminescence properties, solving the technical problem of the lack of left-handed CPL characteristics in existing chiral liquid crystal superstructures.
[0006] To achieve the above objectives, the present application adopts the following technical solution.
[0007] A first aspect of this application provides a chiral liquid crystal superstructure with charge-controlled light-emitting object, comprising a cellulose nanocrystal liquid crystal film and a non-chiral light-emitting object embedded in the cellulose nanocrystal liquid crystal film.
[0008] The non-chiral luminescent object includes any one of carbon dots, organic luminescent small molecules, luminescent polymers, or quantum dots;
[0009] The surface of the non-chiral luminescent object carries a positive or negative charge.
[0010] Preferably, the non-chiral luminescent object is a negatively charged carbon dot, a positively charged carbon dot, or tetrapyridine tetraphenylethylene.
[0011] Preferably, the amount of the non-chiral luminescent object is 0.25 to 1.5 wt% of the mass of the cellulose nanocrystal liquid crystal.
[0012] Preferably, the Zeta potential of the negatively charged chiral luminescent object is adjustable in the range of -20 to 0 mV;
[0013] The Zeta potential of the positively charged non-chiral luminescent object is adjustable in the range of +2 to +25.0 mV.
[0014] A second aspect of this application provides a method for preparing the above-mentioned chiral liquid crystal superstructure, comprising:
[0015] S1, Cellulose nanocrystalline liquid crystals were prepared by sulfuric acid hydrolysis;
[0016] Negatively charged / positively charged carbon dots were synthesized and dispersed in deionized water to obtain a dispersion of negatively charged / positively charged carbon dots;
[0017] S2, adjust the pH of the cellulose nanocrystal liquid crystal to 7.5, and mix the negatively charged carbon dot dispersion with the cellulose nanocrystal liquid crystal evenly to obtain the precursor solution;
[0018] or,
[0019] The pH of the cellulose nanocrystal liquid crystal was adjusted to 2.5, and the positively charged carbon dot dispersion was mixed evenly with the cellulose nanocrystal liquid crystal to obtain the precursor solution.
[0020] S3, the precursor liquid is evaporated to induce self-assembly, dried and then peeled off to form a film, thus obtaining a chiral liquid crystal superstructure.
[0021] Preferably, the preparation of cellulose nanocrystalline liquid crystals by sulfuric acid hydrolysis includes:
[0022] Cellulose powder was added to H2SO4 with a concentration of 45-70 wt%, and reacted at 40-60 °C for 2-3 hours. The reaction was then quenched with cold water.
[0023] The lower suspension was centrifuged and washed, then transferred to a dialysis bag and dialyzed for 7-10 days to obtain a cellulose nanocrystal dispersion.
[0024] The cellulose nanocrystal dispersion was concentrated by evaporation at 40-60 °C to obtain cellulose nanocrystal liquid crystal.
[0025] The molecular weight cutoff of the dialysis bag is 12,000~14,000 Da.
[0026] Preferably, the negatively charged carbon dots are prepared by hydrothermal reaction of citric acid and urea;
[0027] The positively charged carbon dots are prepared by a hydrothermal reaction of citric acid, urea, and polyethyleneimine.
[0028] Preferably, the evaporation-induced self-assembly temperature is 15~80 ℃ and the time is 12~120 h.
[0029] A third aspect of this application provides the application of the chiral liquid crystal superstructure described above or the chiral liquid crystal superstructure prepared by the above preparation method in anti-counterfeiting.
[0030] A fourth aspect of this application provides a circularly polarized luminescent anti-counterfeiting label, prepared by the following method:
[0031] By generating patterns in specific areas of a chiral liquid crystal metastructure thin film, a circularly polarized luminescent anti-counterfeiting label can be obtained.
[0032] The chiral liquid crystal superstructure is the chiral liquid crystal superstructure described above or the chiral liquid crystal superstructure prepared by the above preparation method.
[0033] Compared with the prior art, the beneficial effects of this application are as follows:
[0034] This application provides a universal design path for circularly polarized luminescent materials by controlling the self-assembly kinetics of chiral CNC liquid crystals through the surface charge type and charge density of non-chiral luminescent objects, thereby achieving the control of the final chiral superstructure and its circularly polarized luminescence properties. The preparation method of this application is simple, uses natural and biodegradable raw materials free of heavy metal ions, and has the advantages of being environmentally friendly and sustainable.
[0035] The chiral liquid crystal superstructure with positively charged luminescent guests prepared in this application utilizes the electrostatic crosslinking of positively charged carbon dots to suppress the fusion of CNCs-like crystal aggregates, constructing a supermaterial with a Janus structure. Its lower layer is a homogeneous cholesteric luminescent layer composed of luminescent guests / CNC liquid crystals, and its upper layer is a disordered luminescent layer composed of luminescent guests / CNCs. It breaks through the traditional single-axis limitation, generating left-handed and right-handed CPLs on opposite sides of the same superstructure. The chiral liquid crystal superstructure with negatively charged luminescent guests prepared in this application, consisting of a homogeneous cholesteric luminescent layer composed of luminescent guests / CNC liquid crystals, possesses a long-range ordered cholesteric superstructure and can emit strongly right-handed circularly polarized light.
[0036] The CNC chiral superstructure thin film prepared in this application can realize customized patterns that appear under ultraviolet light and have polarization characteristics, which can be used to make anti-counterfeiting labels to achieve advanced anti-counterfeiting. Attached Figure Description
[0037] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0038] Figure 1 SEM images and circular polarization luminescence properties test results of the CNC chiral superstructure loaded with negatively charged carbon dots prepared in Example 1;
[0039] Figure 2 SEM images and circular polarization luminescence properties test results of the CNC chiral superstructure loaded with positively charged carbon dots prepared in Example 2;
[0040] Figure 3 The image shows the anti-counterfeiting label prepared in Example 3 under ultraviolet light. Detailed Implementation
[0041] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0042] In the following description of this embodiment, the terms "including", "comprising", "having", and "containing" are all open-ended terms, meaning that they include but are not limited to.
[0043] In the following description of this embodiment, the term "and / or" is used to describe the association relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, B existing alone, and A and B existing simultaneously. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0044] In the following description of this embodiment, the term "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0045] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0046] Those skilled in the art should understand that, in the following description of the embodiments of this application, the sequence of numbers does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0047] Those skilled in the art will understand that the numerical ranges in the embodiments of this application should be understood as each intermediate value between the upper and lower limits of the specifically disclosed range. Each smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this application. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0048] Unless otherwise stated, the technical / scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. While this application describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this application. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0049] In a first aspect, this application provides a charge-controlled chiral liquid crystal superstructure, which includes a cellulose nanocrystal (CNC) liquid crystal film and a non-chiral light-emitting object embedded in the cellulose nanocrystal liquid crystal film;
[0050] The achiral luminescent object includes any one of carbon dots, organic luminescent small molecules, luminescent polymers, or quantum dots; the surface of the achiral luminescent object carries a positive or negative charge.
[0051] In this application, the amount of the achiral luminescent guest is 0.25~1.5wt% of the mass of the cellulose nanocrystal liquid crystal. The achiral luminescent guest is preferably a negatively charged carbon dot, a positively charged carbon dot, or a positively charged organic luminescent molecule such as tetrapyridinetetraphenylene.
[0052] In this application, the Zeta potential of the negatively charged achiral luminescent object is adjustable in the range of -20 to 0 mV; the Zeta potential of the positively charged achiral luminescent object is adjustable in the range of +2 to +25.0 mV.
[0053] The chiral liquid crystal superstructure with positively charged luminescent guest prepared in this application utilizes the electrostatic crosslinking effect of positively charged carbon dots (CDs) to suppress the fusion of CNC-like crystal aggregates and construct a supermaterial with a Janus structure. Its lower layer is a uniform cholesteric phase luminescent layer composed of luminescent guest / CNC liquid crystal, and its upper layer is a disordered luminescent layer composed of luminescent guest / CNC. It breaks through the traditional single rotation direction limitation and generates left-handed CPL and right-handed CPL on the front and back sides of the same superstructure, respectively.
[0054] The chiral liquid crystal superstructure with a negatively charged luminescent guest prepared in this application is a uniform cholesteric phase luminescent layer composed of a luminescent guest / CNC liquid crystal. It has a long-range ordered cholesteric phase superstructure and can emit strong right-handed circularly polarized light.
[0055] Secondly, this application provides a method for preparing the above-mentioned chiral liquid crystal superstructure, comprising:
[0056] A second aspect of this application provides a method for preparing the above-mentioned chiral liquid crystal superstructure, comprising:
[0057] S1, Cellulose nanocrystalline liquid crystals were prepared by sulfuric acid hydrolysis;
[0058] Negatively charged / positively charged carbon dots were synthesized and dispersed in deionized water to obtain a dispersion of negatively charged / positively charged carbon dots;
[0059] In this application, the preparation of cellulose nanocrystalline liquid crystals using the sulfuric acid hydrolysis method specifically includes:
[0060] Cellulose powder was added to H2SO4 with a concentration of 45-70 wt% and reacted at 40-60 °C for 2-3 hours. The reaction was then quenched with cold water.
[0061] The lower suspension was centrifuged and washed, then transferred to a dialysis bag and dialyzed for 7-10 days to obtain a cellulose nanocrystal dispersion; wherein the molecular weight cutoff of the dialysis bag was 12000-14000 Da.
[0062] The cellulose nanocrystal dispersion was evaporated and concentrated at 40-60 °C to obtain cellulose nanocrystal liquid crystal.
[0063] In this application, the negatively charged carbon dots are prepared by a hydrothermal reaction of citric acid and urea. Specifically, citric acid and urea are dissolved in deionized water at a mass ratio (or molar ratio), added to a reaction vessel, and reacted at 120-200 °C for 8-10 h. After the reaction, the mixture is cooled to room temperature, the liquid phase is collected by centrifugation, transferred to a dialysis bag with a molecular weight cutoff of 1000 Da, dialyzed for 24 h, and then concentrated using a rotary evaporator to obtain a concentrated solution. The concentrated solution is washed with a mixed solution of deionized water and ethanol, and then freeze-dried to obtain solid negatively charged carbon dots.
[0064] In this application, the positively charged carbon dots are prepared by a hydrothermal reaction of citric acid, urea, and polyethyleneimine. Specifically, citric acid, urea, and polyethyleneimine are dissolved in deionized water in a mass ratio (or molar ratio), added to a reaction vessel, and reacted at 100-200 °C for 8-10 h. After the reaction, the mixture is cooled to room temperature, the liquid phase is collected by centrifugation, transferred to a dialysis bag with a molecular weight cutoff of 1000 Da, dialyzed for 24 h, and then concentrated using a rotary evaporator to obtain a concentrated solution. The concentrated solution is washed with a mixed solution of deionized water and ethanol, and then freeze-dried to obtain solid positively charged carbon dots.
[0065] S2, adjust the pH of the cellulose nanocrystal liquid crystal to 7.5, and mix the negatively charged carbon dot dispersion with the cellulose nanocrystal liquid crystal evenly to obtain the precursor solution;
[0066] or,
[0067] The pH of the cellulose nanocrystal liquid crystal was adjusted to 2.5, and the positively charged carbon dot dispersion was mixed evenly with the cellulose nanocrystal liquid crystal to obtain the precursor solution.
[0068] In this application, the pH value is adjusted by adding KOH or hydrochloric acid to the CNC liquid crystal.
[0069] Specifically, KOH solution is added to the CNC liquid crystal until the pH of the CNC dispersion is approximately 7.0. The CNC dispersion (pH ≈ 7.0) is then dialyzed for one week to remove K. + A CNC liquid crystal with a pH of 7 was obtained; it was then concentrated to obtain a CNC liquid crystal of a specific concentration. Alternatively, hydrochloric acid was added to the CNC liquid crystal to adjust the pH to 2.5, resulting in a CNC liquid crystal with a pH of 2.5; this was then concentrated to obtain a CNC liquid crystal of a specific concentration.
[0070] In this application, a negatively charged / positively charged carbon dot dispersion is added to a CNC liquid crystal, mixed using a vortex mixer, and intermittently ultrasonicated using a 6 mm diameter probe (240 W, 2 s on / 1 s off), with an ultrasonication time of 64 s·g. -¹, and then subjected to external cooling. Subsequently, the mixture was stirred at 1000 rpm for 6 h to obtain either a negatively charged carbon dot / CNC liquid crystal precursor solution or a positively charged carbon dot / CNC liquid crystal precursor solution.
[0071] S3, the mixture is subjected to evaporation-induced self-assembly, dried and then peeled off to form a film, thus obtaining a chiral liquid crystal superstructure.
[0072] Specifically, the obtained precursor solution is poured into a polystyrene petri dish, and the dish is covered at 15–80 °C to allow it to slowly evaporate for 12–120 h. Then the lid is removed, and the dish is further evaporated at 25 °C for 12 h to remove any remaining moisture, thus obtaining the chiral CNC liquid crystal superstructure.
[0073] This application provides a universal design path for circularly polarized light-emitting materials by controlling the self-assembly dynamics of chiral CNC liquid crystals by adjusting the surface charge type and charge density of non-chiral light-emitting objects, thereby achieving the control of the final chiral superstructure and its circularly polarized light-emitting properties.
[0074] Furthermore, the preparation method of this application is simple, the raw materials are natural and biodegradable substances, and there are no heavy metal ions, which has the advantages of being environmentally friendly, green and sustainable.
[0075] The chiral liquid crystal superstructure thin film with a positively charged luminescent object of this application emits left-handed circularly polarized light from its front side and right-handed circularly polarized light from its back side; the chiral liquid crystal superstructure with a negatively charged luminescent object prepared in this application can emit strong right-handed circularly polarized light; both can be used for advanced anti-counterfeiting.
[0076] This application also provides a circularly polarized luminescent anti-counterfeiting label, which is prepared by the following method:
[0077] A circularly polarized luminescent anti-counterfeiting label is obtained by generating a pattern in a specific area of a chiral liquid crystal superstructure thin film; wherein the chiral liquid crystal superstructure is the chiral liquid crystal superstructure described above or the chiral liquid crystal superstructure prepared by the above preparation method.
[0078] Specifically, using embossing or masking methods, specific areas of a hand-type liquid crystal superstructure film are treated with acid or alkali to generate a specific pattern on its surface. After the acid / alkali-treated areas are naturally dried, a circularly polarized luminescent anti-counterfeiting label is obtained. The circularly polarized luminescent anti-counterfeiting label has a customizable pattern that emits strong circularly polarized light, creating a sharp contrast with the "background" area; alternatively, the pattern can emit weak circularly polarized light, while the "background" area emits strong circularly polarized light.
[0079] The present application will be further described below through specific embodiments.
[0080] Example 1
[0081] This embodiment provides a method for fabricating a CNC chiral superstructure loaded with negatively charged carbon dots, including:
[0082] S1, Synthesis of CNC liquid crystal: 20 g of cellulose powder was added to 350 mL of 64 wt% H2SO4 and reacted at 50°C for 2.0 h, followed by quenching with cold deionized water. The lower suspension was centrifuged and washed twice at 6000 rpm, then transferred to a dialysis bag (molecular weight cutoff: 12000-14000 Da) and dialyzed for one week. The CNC dispersion was concentrated at 40°C using a rotary evaporator to obtain a CNC liquid crystal with a concentration of 3.0 wt%.
[0083] Synthesis of negatively charged carbon dots: 1.5368 g of citric acid and 1.4415 g of urea were dissolved in 40 mL of deionized water and transferred to a 100 mL polytetrafluoroethylene-lined reactor. The reaction was carried out at 160 °C for 8 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged at 11000 rpm for 10 min. The liquid phase was collected and transferred to a dialysis bag with a molecular weight cutoff of 1000 Da. Dialysis was performed for 24 h to obtain a carbon dot dispersion. The carbon dot dispersion was concentrated and washed with a mixture of deionized water and ethanol, repeated five times. The dispersion was then freeze-dried to obtain solid negatively charged carbon dots. The solid negatively charged carbon dots were dispersed in deionized water to prepare a carbon dot solution with a solid content of 5 mg / mL.
[0084] S2, take 40 mL of 3.0 wt% CNC liquid crystal and add 0.5 M KOH solution dropwise under magnetic stirring until the pH of the CNC liquid crystal is ≈7.0; dialyze the CNC liquid crystal (pH≈7.0) for one week to remove K. + The CNC liquid crystal was concentrated using a rotary evaporator to obtain a CNC liquid crystal with a concentration of 6.0 wt% (pH≈7.0).
[0085] 80 μL of carbon dot solution was added to 1.33 g of CNC liquid crystal (6 wt%), mixed using a vortex mixer, and intermittently sonicated using a 6 mm diameter probe (240 W, 2 s on / 1 s off) for 64 s·g. - ¹, and then subjected to external cooling. Subsequently, it was vigorously stirred at 1000 rpm for 6 h to finally obtain 0.50 wt% negatively charged carbon dot / CNC liquid crystal precursor solution.
[0086] S3. Pour the precursor solution into a polystyrene petri dish with a diameter of 3.5 cm, cover it, and allow it to evaporate slowly. After 4 days, remove the cover and continue evaporating at 25 °C for about 0.5 days to remove the remaining moisture, thus obtaining the CNC chiral superstructure loaded with negatively charged carbon dots.
[0087] Example 2
[0088] This embodiment provides a method for fabricating a CNC chiral superstructure loaded with positively charged carbon dots, including:
[0089] S1, Synthesizing CNC liquid crystal: Same as in Example 1;
[0090] Synthesis of positively charged carbon dots: 1.5368 g citric acid, 1.4415 g urea, and 1.5368 g polyethyleneimine were dissolved in 40 mL of deionized water and transferred to a 100 mL polytetrafluoroethylene-lined reactor. The reaction was carried out at 160 °C for 8 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged at 11000 rpm for 10 min. The liquid phase was collected and transferred to a dialysis bag with a molecular weight cutoff of 1000 Da. Dialysis was performed for 24 h to obtain a carbon dot dispersion. The carbon dot dispersion was concentrated and washed with a mixture of deionized water and ethanol, repeated five times. The dispersion was then freeze-dried to obtain solid positively charged carbon dots. The positively charged carbon dots were dispersed in deionized water to prepare a carbon dot solution with a solid content of 5 mg / mL.
[0091] S2, take 40 mL of CNC liquid crystal with a concentration of 3.0 wt%, add hydrochloric acid dropwise under magnetic stirring to adjust the pH of the CNC liquid crystal to 2.5; concentrate the CNC liquid crystal using a rotary evaporator to obtain a CNC liquid crystal with a concentration of 6.0 wt% (pH≈2.5).
[0092] 80 μL of carbon dot solution was added to 1.33 g of CNC liquid crystal (6 wt%), mixed using a vortex mixer, and intermittently sonicated using a 6 mm diameter probe (240 W, 2 s on / 1 s off) for 64 s·g. - ¹, and then subjected to external cooling. Subsequently, it was vigorously stirred at 1000 rpm for 6 h to finally obtain 0.50 wt% positively charged carbon dot / CNC liquid crystal precursor solution.
[0093] S3. Pour the precursor solution into a polystyrene petri dish with a diameter of 3.5 cm, cover it, and allow it to evaporate slowly. After 4 days, remove the cover and continue evaporating at 25 °C for about 0.5 days to remove the remaining moisture, thus obtaining a CNC chiral superstructure loaded with positively charged carbon dots.
[0094] Example 3
[0095] This embodiment provides a method for preparing a circularly polarized luminescent anti-counterfeiting label, including:
[0096] 0.5 M hydrochloric acid was dropped onto a relief stamp engraved with a rose pattern to imprint the positively charged carbon dot-loaded CNC chiral superstructure of Example 2. The stamp was removed after 20 s.
[0097] After the area to be imprinted dries naturally, the circularly polarized luminescent anti-counterfeiting label is obtained.
[0098] The chiral liquid crystal superstructure thin films prepared in Examples 1 and 2 were characterized and their performance evaluated as follows:
[0099] Figure 1 The images show the structural characterization and circularly polarized luminescence properties of the negatively charged carbon dot-loaded CNC chiral superstructure prepared in Example 1; whereby... Figure 1 Figure a shows a cross-sectional scanning electron microscope image. Figure 1 Figure b shows the circularly polarized emission spectrum.
[0100] from Figure 1 It can be seen that the negatively charged carbon dot-loaded CNC chiral superstructure prepared in Example 1 has a long-range ordered cholesteric phase superstructure and can emit strong right-handed circularly polarized light.
[0101] Figure 2 The structural characterization and circular polarization luminescence properties of the positively charged carbon dot-loaded CNC chiral superstructure prepared in Example 2 are shown in the following figures; Figure 2 Figure a shows a cross-sectional scanning electron microscope image. Figure 2 Figure b shows the circularly polarized emission spectrum.
[0102] from Figure 2 It can be seen that the positively charged carbon dot-loaded CNC chiral superstructure prepared in Example 2 has a long-range ordered cholesteric phase superstructure at the bottom and a disordered structure at the top, exhibiting a Janus structure. The front side of this chiral superstructure emits left-handed circularly polarized light, and the back side can emit right-handed circularly polarized light.
[0103] The anti-counterfeiting label prepared in Example 3 is shown in the image under ultraviolet light. Figure 3 As shown. From Figure 3 It can be seen that the anti-counterfeiting label prepared in Example 3 can show a distinct rose pattern under ultraviolet light. The "rose" area emits almost no circularly polarized light, while the "background" area emits strong right-handed circularly polarized light.
[0104] Although this application has been described in detail in this specification with general descriptions and specific embodiments, some modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, such modifications or improvements made without departing from the spirit of this application are all within the scope of protection claimed in this application.
Claims
1. A chiral liquid crystal superstructure of light emitting guest charge regulation, characterized in that, It comprises a cellulose nanocrystal liquid crystal film, and an achiral luminescent guest embedded in the cellulose nanocrystal liquid crystal film; The achiral luminescent guest comprises any one of carbon dots, organic luminescent small molecules, luminescent polymers or quantum dots; The achiral luminescent guest is positively or negatively charged on the surface.
2. The chiral liquid crystal superstructure of claim 1, wherein, The achiral luminescent guest is negatively charged carbon dots, positively charged carbon dots or tetraphenylstyrene.
3. The chiral liquid crystal superstructure of claim 1, wherein, The amount of the achiral luminescent guest is 0.25-1.5 wt% of the cellulose nanocrystal liquid crystal.
4. The chiral liquid crystal superstructure of claim 1, wherein, The Zeta potential of the negatively charged achiral luminescent guest is regulated in the range of -20-0 mV. The Zeta potential of the positively charged achiral luminescent guest is regulated in the range of +2-+25.0 mV.
5. The method of claim 1, wherein the chiral liquid crystal superstructure is prepared by the steps of: It comprises: S1, preparing a cellulose nanocrystal liquid crystal by a sulfuric acid hydrolysis method; Synthesizing negatively / positively charged carbon dots and dispersing them in deionized water to obtain a negatively / positively charged carbon dot dispersion; S2, adjusting the pH of the cellulose nanocrystal liquid crystal to 7.5, uniformly mixing the negatively charged carbon dot dispersion with the cellulose nanocrystal liquid crystal to obtain a precursor solution; Alternatively, Adjusting the pH of the cellulose nanocrystal liquid crystal to 2.5, uniformly mixing the positively charged carbon dot dispersion with the cellulose nanocrystal liquid crystal to obtain a precursor solution; S3, evaporating the precursor solution to induce self-assembly, and peeling off the film after drying to obtain a chiral liquid crystal superstructure.
6. The production method according to claim 5, characterized in that, The sulfuric acid hydrolysis method for preparing the cellulose nanocrystal liquid crystal comprises: adding cellulose powder into H2SO4 with a concentration of 45-70 wt% and reacting at 40-60 °C for 2-3 h, and quenching the reaction with cold water; centrifuging and washing the lower suspension, and then transferring it to a dialysis bag for dialysis for 7-10 d to obtain a cellulose nanocrystal dispersion; evaporating and concentrating the cellulose nanocrystal dispersion at 40-60 °C to obtain a cellulose nanocrystal liquid crystal; wherein the dialysis bag has a molecular weight cut-off of 12000-14000 Da.
7. The production method according to claim 5, characterized by, The negatively charged carbon dots are prepared by hydrothermal reaction of citric acid and urea; The positively charged carbon dots are prepared by hydrothermal reaction of citric acid, urea and polyethyleneimine.
8. The production method according to claim 5, characterized by, The temperature of the evaporation-induced self-assembly is 15-80 °C, and the time is 12-120 h.
9. The chiral liquid crystal superstructure of claims 1-4 or prepared by the preparation method of claims 5-8 for use in anti-counterfeiting.
10. A circularly polarized luminescent anti-counterfeiting label, characterized in that, It is prepared by the following method: a circularly polarized luminescent anti-counterfeiting label is obtained by generating a pattern in a specific area of the chiral liquid crystal superstructure film; The chiral liquid crystal superstructure is the chiral liquid crystal superstructure of claims 1-4 or prepared by the preparation method of claims 5-8.
